2008
DOI: 10.1002/jssc.200700275
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of the headspace‐solid phase microextraction for organomercury and organotin compound determination in sediment and biota

Abstract: Headspace solid-phase microextraction was optimised for the simultaneous preconcentration of methylmercury (MeHg+), monobutyltin, dibutyltin, tributyltin, monophenyltin (MPhT), diphenyltin (DPhT), and triphenyltin (TPhT) from sediments and biota. Extraction time (3-24 min), extraction temperature (20-90 degrees C), desorption time (1-10.4 min), desorption temperature (152-260 degrees C), and sample volume (5-22 mL) were simultaneously optimised, while variables such as fibre type (30 microm polydimethylsiloxan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Different procedures have been developed for the determination of organometallic and inorganic compounds of tin, mercury, selenium, arsenic, lead, manganese and other metals [20][21][22][23][24][25][26][27][28][29][30][31]. Mercury is one of the most toxic elements impacting on human and ecosystem health and therefore is one of the most studied environmental pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Different procedures have been developed for the determination of organometallic and inorganic compounds of tin, mercury, selenium, arsenic, lead, manganese and other metals [20][21][22][23][24][25][26][27][28][29][30][31]. Mercury is one of the most toxic elements impacting on human and ecosystem health and therefore is one of the most studied environmental pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…It is easy to follow and has been used in several analytical applications [6,7]. The aim of this work was to further optimize the factors affecting chromatographic separation and dansyl derivatization by MultiSimplex, and to apply the method for simultaneous measurement of RIP, 9-OH-RIP and the NTs in human urine samples.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been reported for the determination of organotin compounds in sediment , bodily fluids , seawater , and marine biota samples . Little has been reported so far on tin speciation in different kinds of edible vegetable oils.…”
Section: Introductionmentioning
confidence: 99%